Interactive 2D vs. 3D Loading Screens in VR: Impact on User Experience and Perceived Wait Time - Freitas, Gustavo Machado de; Berwaldt, Natan Luiz Paetzhold; Domenico, Gabriel Di; Cossetin Neto, Alfredo; Pozzer, Cesar Tadeu (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Loading screens in games and VR tend to be frustrating, so optimizing them to maintain user engagement is crucial. Previous research suggests that interactions can significantly reduce perceived wait time. However, the complexity of 3D interactions may impose additional computational overhead. To address this, we investigate the possibility of using interactive loading screens with 2D elements, aiming to balance user engagement and performance. Through a user study, with 21 participants, and performance benchmarks, we evaluate the effectiveness of this technique in enhancing UX and reducing perceived wait times. Our findings indicate that interactive 2D screens, while less computationally intensive, can offer comparable user engagement benefits to fully interactive 3D screens, providing a viable alternative for optimizing VR loading experiences.